Parental Psychological Control: Maternal, Adolescent, and Contextual Predictors - Pérez, J. Carola; Huerta, Paula; Rubio, Bernardita; Fernández, Olga (Frontiers in Psychology, 2021)
Parental psychological control hinders the development of autonomy, identity formation, and the attainment of self-determination and individuation of adolescents. The aim of this study was to deepen the understanding of which conditions increase the risk of the use of maternal psychological control by simultaneously considering the contribution of adolescent temperament, maternal separation anxiety, and adolescents’ perception of interparental conflict. A correlational study involving a sample of 106 Chilean adolescent-mother dyads was done. Adolescents were, on average, 15.42 years old (SD= 1.09) and 77% male. Mothers were, on average, 45.46 years old (SD= 6.39). We administered self-report questionnaires to the adolescent measuring effortful control and frustration as temperamental dimensions, along with the perception of interparental conflict. Mothers reported on their separation anxiety. Both the adolescents and their mothers reported on the use of parental psychological control. Adolescents reported higher levels of maternal psychological control than their mothers did. All predictors were associated with psychological control reports. Higher levels of maternal anxiety about adolescent distancing, inter-parental conflict, and adolescent frustration were associated with higher reported levels of psychological control. In contrast, higher levels of adolescent effortful control were associated with lower levels of maternal psychological control. Finally, when maternal separation anxiety and inter-parental conflict were high there was a higher use of maternal psychological control. The present findings inform on how adolescent's self-regulatory skills could reduce the risk of being exposed to maternal psychological control. And highlight the importance of using a systemic and interactional conceptualization when trying to understand their use.